2014
DOI: 10.5539/sar.v4n1p13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Application of Liquid Swine Manure on Soil Organic Carbon and Enzyme Activities in Two Contrasting Saskatchewan Soils

Abstract: Repeated application of animal manure to agricultural fields as a source of plant nutrients has led to questions concerning the impact of this practice on soil organic carbon (C) and biochemical properties, specifically the activity of soil enzymes. There are also some environmental concerns of using livestock manure. The objectives of this study were to determine the effects of repeated applications of liquid swine manure (LSM) on total organic C (TOC), light fraction organic C (LFOC) and on the activity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(28 reference statements)
0
5
0
1
Order By: Relevance
“…In the present study, the amounts of soil TOC in the 0–10 cm depth were greater under the ORG than the CONV cropping system. This was probably due to the application of manure in the organic cropping system (Campbell et al ., 1986; McGill et al ., 1986; Yanan et al ., 1997; Whalen et al ., 2001; Assefa et al ., 2004; Heitkamp et al ., 2011; King et al ., 2015). Similarly, research in Saskatchewan, Canada, has also shown that ORG cropping systems, which include application of manure, can increase organic C and N, and availability of nutrients in soil even after short-term (3 years) additions (Malhi, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the amounts of soil TOC in the 0–10 cm depth were greater under the ORG than the CONV cropping system. This was probably due to the application of manure in the organic cropping system (Campbell et al ., 1986; McGill et al ., 1986; Yanan et al ., 1997; Whalen et al ., 2001; Assefa et al ., 2004; Heitkamp et al ., 2011; King et al ., 2015). Similarly, research in Saskatchewan, Canada, has also shown that ORG cropping systems, which include application of manure, can increase organic C and N, and availability of nutrients in soil even after short-term (3 years) additions (Malhi, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Probability of significance for tested treatment effects of tillage, cropping system and tillage × cropping system interaction on total organic C (TOC), total organic N (TON), light fraction organic C (LFOC), light fraction organic N (LFON), pH, mineralizable N (N min ), nitrate-N (NO 3 -N), ammonium-N (NH 4 -N) and extractable P in the 0-10, 10-20, 20-30, 0-20 and 0-30 cm soil depths in autumn 2010 (after 24 growing seasons) in a field experiment established in autumn 1987 at La Pocatière, Québec, Canada system. This was probably due to the application of manure in the organic cropping system (Campbell et al, 1986;McGill et al, 1986;Yanan et al, 1997;Whalen et al, 2001;Assefa et al, 2004;Heitkamp et al, 2011;King et al, 2015). Similarly, research in Saskatchewan, Canada, has also shown that ORG cropping systems, which include application of manure, can increase organic C and N, and availability of nutrients in soil even after short-term (3 years) additions (Malhi, 2012).…”
Section: Soil Organic Carbon and Nitrogenmentioning
confidence: 99%
“…Animal effluent is a byproduct of animal farms and a concern for CAFOs (concentrated animal feeding operations) due to the significant resources required for environmental management of the waste. The effluent is also a valuable source of organics and nutrients for plants, cropland, and pastures (Broetto et al, 2014;Gollehon et al, 2001;King et al, 2015).…”
Section: Swine Lagoon Effluentmentioning
confidence: 99%
“…This is often accomplished by applying effluent to fields of farmers who own nearby fields. Several studies have shown increases in both macro-and micro-nutrients after effluent applications (Broetto et al, 2014;DeRouchey et al, 2009;Gollehon et al, 2001;Hountin et al, 1997;Marr and Facey, 1995;Schoenau, 2006) but this isn't always beneficial for the crops or pasture, as the application rates can be too low to provide optimal nutrients for plant growth (Broetto et al, 2014;Gollehon et al, 2001) and responses in soil samples may not show after an initial application but only after a continued series of applications (Hountin et al, 1997;King et al, 2015). Low concentrations of nitrogen in the effluent may be caused by volatilization prior to field application.…”
Section: Swine Lagoon Effluentmentioning
confidence: 99%
“…돈분 액비의 장기 연용은 토양 유 기물 함량 증가에 효과가 있을 뿐만 아니라 토양 미생물 효 소 활성 유도에 기여한다 (Adeli et al, 2008;King et al, 2015). 지난 10여년 전만해도 가축분뇨 액비의 처리 및 이용에 관한 연구는 대부분 벼와 노지 밭작물에 대한 밑거름 적정 시용량 및 수량성 조사였다 (Jeon et al, 2003;Kim et al, 1999;Lim et al, 2002;Park et al, 2001).…”
unclassified